1990
DOI: 10.1037/1040-3590.2.4.451
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional assessment of parent-adolescent relations.

Abstract: This document is copyrighted by the American Psychological Association or one of its allied publishers.This article is intended solely for the personal use of the individual user and is not to be disseminated broadly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 9 publications
2
41
0
Order By: Relevance
“…First, they replicate earlier findings of a positive association between stress, in the form of interpersonal disagreements, and internalizing symptoms. 27,33,34 They extend earlier work by demonstrating a positive link between changes in disagreements and changes in symptoms. Specifically, we found that families reporting intensifying parent-adolescent disagreements over time usually included an adolescent who reported increasing internalizing symptoms over that same period.…”
Section: Hypothesis Testingsupporting
confidence: 64%
“…First, they replicate earlier findings of a positive association between stress, in the form of interpersonal disagreements, and internalizing symptoms. 27,33,34 They extend earlier work by demonstrating a positive link between changes in disagreements and changes in symptoms. Specifically, we found that families reporting intensifying parent-adolescent disagreements over time usually included an adolescent who reported increasing internalizing symptoms over that same period.…”
Section: Hypothesis Testingsupporting
confidence: 64%
“…Self-reported family conflict was assessed through the Parent Adolescent Relationship Questionnaire (PARQ), a multidimensional measure with true/false items tapping overt conflict, belief systems, and family structure (Robin, Koepke, & Moye, 1990). Parents and adolescents independently completed the PARQ.…”
Section: Methodsmentioning
confidence: 99%
“…Two scores were used for each family member: (1) General Conflict-a factorially based linear composite of 45 items tapping Communication (e.g., "My mom puts me down"), Problem Solving ("We think of many good ideas to solve our problems"), and Warmth/Hostility scales ("Quite honestly, I hate my dad"); and (2) Conflict Over Eating-I4 items assessing overt conflict and hostility concerning eating, mealtimes, and food ("I dread mealtimes with my daughter"; "We argue often about food and eating"). Previous research has demonstrated the internal consistency, criterion-related validity, and construct validity of these PARQ scores (Robin et al, 1990).…”
Section: Methodsmentioning
confidence: 99%
“…The PARQ (Robin, Koepke, & Moye, 1990) is a measure of the relationship between parents and adolescents. There are parent and adolescent forms that use a true/false format.…”
Section: Methodsmentioning
confidence: 99%